2015
DOI: 10.1016/j.jtcvs.2015.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen ameliorates pulmonary hypertension in rats by anti-inflammatory and antioxidant effects

Abstract: Molecular hydrogen ameliorates MCT-induced PAH in rats by suppressing macrophage accumulation, reducing oxidative stress and modulating the STAT3/NFAT axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
(39 reference statements)
2
33
1
3
Order By: Relevance
“…MCT induces severe PAH and this animal model imitates certain key characteristics of human PAH, including pulmonary vascular remodeling, PASMC proliferation, and oxidative stress [37], [38]. In this study, our data revealed that 4-HNE levels were significantly elevated in the lungs of rats with MCT-induced PAH and that 4-HNE promoted the proliferation and migration of HPASMCs in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…MCT induces severe PAH and this animal model imitates certain key characteristics of human PAH, including pulmonary vascular remodeling, PASMC proliferation, and oxidative stress [37], [38]. In this study, our data revealed that 4-HNE levels were significantly elevated in the lungs of rats with MCT-induced PAH and that 4-HNE promoted the proliferation and migration of HPASMCs in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…Since Ohsawa et al5 reported that hydrogen could be used in antioxidant therapy, numerous studies have confirmed that molecular hydrogen is a medical gas with beneficial effects on oxidative stress, inflammation, apoptosis, lipid metabolism, and signaling pathways 11. Basic studies and clinical studies have demonstrated that hydrogen ameliorates the pathological conditions in numerous human diseases or disease models in animals 111213. In available studies, hydrogen is administered through the oral intake of hydrogen water,14 intravenous infusion of hydrogen-rich saline15 and inhalation of air with 2-4% hydrogen gas 16.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hydrogen have also been reported in lung injuries secondary to intestinal ischemia/reperfusion and extensive skin burn . We and others have recently reported that hydrogen is also effective for pulmonary hypertension . The effects of hydrogen have been also reported in perinatal disorders: neonatal cerebral hypoxia; LPS‐induced fetal lung injury; preeclampsia; and perinatal brain injury caused by prenatal inflammation …”
Section: Introductionmentioning
confidence: 91%